(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
The paper examines the notion of habits from the perspective of a pathic aesthetics based on the neo-phenomenological theory of Leib (felt body) and its ubiquitous communication. By questioning whether experience should be considered as a confirmation or a failure of expectation, it shows the inextricable intertwining of the unexpected and routine in our involuntary life experience and delves into a well known phenomenological crux: is the lived or felt body what is subject to self-affection and proprioception or rather the “absent” body, which is always transcended in its being-for-other (transitivity)? The assumption then that felt-bodily habits are formed through a motor scheme depending on its being a perfect pre-reflective resonance (especially thanks to its more or less stable “felt-bodily islands”) of outside atmospheric feelings and affordances that also becomes a true “style”, is finally examined by showing the points of both contact and discrepancy between a New Phenomenology (Hermann Schmitz) focused above all on the rediscovery (in a critical function) of the archaic dimension of the Leib and a melioristic Somaesthetics (Richard Shusterman) pragmatically interested in a more creative individual self-stylisation.